Dr. Strange Geo-Blocking Love Or: How The E.U. Learned To Stop Worrying About Cultural Integration And Love The TV Trade Barrier - Zareh, Batia M. (The Columbia Journal of Law & the Arts, 2018)
The E.U. Antitrust Case that opened on July 23, 2015 against Sky U.K. and six American studios—Disney, Fox, NBCUniversal, Paramount Pictures, Sony and Warner Brothers—has its structural roots in the Television Without Frontiers Directive, which was vigorously debated as a last-minute standoff that threatened to derail the conclusion of the GATT Uruguay Round of trade negotiations and is still considered to be the cornerstone of the European Union’s audiovisual policy. This Article examines the unique history of a Cultural Exception with respect to audiovisual works as applied in trade negotiations to Hollywood film and television productions, and argues that, rather than violating E.U. regulations, the decades-old practice of regional contractual restrictions and geo-blocking is both consistent with and a direct result of the E.U.’s protectionist and paternalistic efforts to shield its individual member states’ local production entities from competition and its populations from a perceived and decidedly unwelcomed Svengali-like juggernaut of American cultural influence. The E.U. antitrust action is therefore in direct contravention to the spirit of the trade laws over which Hollywood studios were so stridently subjected to debating and is inconsistent with stated E.U. audiovisual norms. Abolishing regional access limitations will put the future of the E.U.’s various local distributors at risk, for the existing patchwork of distribution related rules impacting foreign property directly impacts American producers’ decisions regarding whether and how to continue to do business in the region. Thus, any attempt to implement the E.C.’s aspirational Digital Single Market 2020 target terms must be reconciled in light of the current political climate in Europe and global technological capabilities if the E.U. is to remain a relevant market at the forefront of the modern entertainment industry and continue to benefit from the uniquely privileged relationship it has enjoyed for nearly a century with its many Hollywood studio production partners.